Neonatal Leuconostoc lactis meningitis - Arumugam, Senthil Kumar; Govindharaj, Kaviyarasan (International Journal of Contemporary Pediatrics, 2021)
Leuconostoc lactis has a low potential for human infection, although serious infections have been documented in immunocompromised persons. The source of this organism is a dairy product. A 3-day old neonate was presented with multifocal clonic seizures who were given formula feed from birth. We isolated Leuconostoc lactis in his Cerebrospinal fluid (CSF), which is resistant to vancomycin. L. lactis meningitis was treated successfully with the injection of ampicillin-sulbactam.